Natural radiation monitoring and control treatment in the Hantepe beach - Gunduz, H.; Tukenmez, I.; Cetiner, M. A. (Oxford University Press (OUP), 2012)
This work has been carried out to monitor and decrease the natural radiation exposure at the Hantepe beach (Çanakkale, Turkey). A 0.25- to 0.30-m-thick layer of sand was scraped, removed and deposited in a safe place in order to decrease people's exposure to radiation and to relieve relevant radiophobia. The original mean value of dose rate on the beach was 1.38 μGy h(-1) at the contact and 1.0 μGy h(-1) at 1 m above the ground. After the scraping process, the mean value of dose rate decreased to 0.98 μGy h(-1) at the contact and to 0.78 μGy h(-1) at 1 m above the ground. One year later, these values decreased to 0.70 μGy h(-1) at the contact and to 0.56 μGy h(-1) at 1 m above the ground. The effective original dose rate of 1.2 mSv y(-1) decreased to 0.95 mSv y(-1) after the surface treatment and to 0.69 mSv y(-1) one year later.
Keywords: Radioisotopes; Radiation Protection; Turkey; Radiation Monitoring; Background Radiation; Soil Pollutants, Radioactive; Environmental Exposure; Bathing Beaches; 6. Clean water